2019
DOI: 10.1159/000504839
|View full text |Cite
|
Sign up to set email alerts
|

Switching Biologics in the Treatment of Psoriasis: A Multicenter Experience

Abstract: Background/Objective: The purpose of our study was to provide evidence on the treatment choices, reasons, and results of switching between biologic agents in treating patients with psoriasis. Methods: We conducted a retrospective database search of six tertiary referral centers for pso­riasis patients between January 2007 and May 2019. We analyzed patient and treatment characteristics of all patients in the registry. Results: We enrolled 427 psoriatic patients treated with biologics, and 145 (34%) required a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 29 publications
(36 reference statements)
2
18
0
1
Order By: Relevance
“…In clinical practice, modifications of dosing regimens, 9–13 intermittent therapy, or interruption followed by retreatment 14,15 have been reported to impact treatment effectiveness. Biologic switches in the treatment of PsO have been evidenced to be mostly due to a lack of efficacy, to adverse events (AE) to a lesser extent, or to efforts to achieve better clinical response 6,10,15–19 . Specific to Canadian real‐world practices, off‐label regimens are less likely to include biologics dose reductions or interval increases compared with other practices worldwide such as European practices 11 …”
Section: Introductionmentioning
confidence: 99%
“…In clinical practice, modifications of dosing regimens, 9–13 intermittent therapy, or interruption followed by retreatment 14,15 have been reported to impact treatment effectiveness. Biologic switches in the treatment of PsO have been evidenced to be mostly due to a lack of efficacy, to adverse events (AE) to a lesser extent, or to efforts to achieve better clinical response 6,10,15–19 . Specific to Canadian real‐world practices, off‐label regimens are less likely to include biologics dose reductions or interval increases compared with other practices worldwide such as European practices 11 …”
Section: Introductionmentioning
confidence: 99%
“…16 Although the scientific basis is not clear yet, switching from one anti-TNF agent to another may be an effective therapeutic option. 17 The efficacy of biological treatments in psoriasis has been shown in numerous clinical trials. However, these results may not always be compatible with real-life data.…”
Section: Discussionmentioning
confidence: 99%
“…A randomized, double‐blinded, placebo‐controlled, 16‐week study of 282 patients showed that switching from another anti‐TNF agent to adalimumab resulted in a significant improvement in PASI scores 16 . Although the scientific basis is not clear yet, switching from one anti‐TNF agent to another may be an effective therapeutic option 17 …”
Section: Discussionmentioning
confidence: 99%
“…Clinical improvement (reduction of PASI and BSA) after biological treatment in psoriasis with nail involvement may be slower than in psoriasis with no nail involvement. A drug switch is also required more frequently [29][30][31]. Nevertheless, biological drugs seem to be more effective than classic drugs.…”
Section: Nail Psoriasismentioning
confidence: 99%
“…Poprawa kliniczna (redukcja PASI i BSA) po leczeniu biologicznym w łuszczycy z zajęciem paznokci może być wolniejsza niż w łuszczycy bez zajęcia płytek paznokciowych. Częściej wymagana jest również zmiana leku [29][30][31]. Leki biologiczne wydają się jednak skuteczniejsze niż leki klasyczne.…”
Section: łUszczyca Paznokciunclassified